PENGARUH KECERDASAN SPIRITUAL TERHADAP KETERLIBATAN KERJA DAN KEPUASAN KERJA YANG DIMEDIASI OLEH PEMBERDAYAAN PSIKOLOGIS PADA PERAWAT RSUD MEURAXA KOTA BANDA ACEH - Savira Ismaryadi; Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to measure the effect of Spiritual Intelligence on Job Engagement and Job Satisfaction with Psychological Empowerment as a mediation variable for Nurses of Meuraxa Hospital in Banda Aceh. The sample used in this research were nurses of Meuraxa Hospital in Banda Aceh wich amounted to 159 respondents. The data collection equipment used in this study is a questionnaire. The sampling technique used is Probability Sampling. Structural Equation Model (SEM) is used as a method of analysis to determine the effect of all the variables involved. Based on the result of SEM analysis, indicate that  Spiritual Intelligence has a positive effect on Job Engagement, Spiritual Intelligence has no positive effect to Job Satisfaction, Spiritual Intelligence has a positive effect on Psychological Empowerment, Psychological Empowerment has a positive effect on Job Engagement, Psychological Empowerment has a positive effect on Job Satisfaction, and Psychological Empowerment mediate Spiritual Intelligence to Job Engagement, and also mediate Spiritual Intelligence to Job Satisfaction.